2003
DOI: 10.1023/b:doop.0000005338.51554.e3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in photopic OPs occurring with vigabatrin treatment

Abstract: Early photopic OPs were disrupted more than the late OP, suggesting relative deficit in the ON (depolarizing) retinal pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Some of these electrophysiologic indicators are likely to reflect the changing retinal nontoxic GABA levels. 20,21 For example, oscillatory potentials decrease in amplitude during drug treatment but recover after discontinuation of the drug, unlike the decrease in flicker amplitude, which is less likely to recover. 22 Most children in the HSC longitudinal study do not show the form of retinal nerve fiber layer atrophy described in these 3 more advanced cases of retinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these electrophysiologic indicators are likely to reflect the changing retinal nontoxic GABA levels. 20,21 For example, oscillatory potentials decrease in amplitude during drug treatment but recover after discontinuation of the drug, unlike the decrease in flicker amplitude, which is less likely to recover. 22 Most children in the HSC longitudinal study do not show the form of retinal nerve fiber layer atrophy described in these 3 more advanced cases of retinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Because a variety of ERG parameters (amplitude and implicit time) change during vigabatrin treatment, the current studies are helping to clarify which of these changes represent nontoxic side effects and which correlate with drug toxicity. [20][21][22] Changes in oscillatory potential amplitude result, at least in part, from non-toxic changes. 22 Conversely, if the ERG, particularly the 30-Hz flicker response, decreases more than expected from intervisit variability, both the clinical assessment and the ERG are repeated within 3 months.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…59 Numerous investigators have reported the prevalence in children to be well below that of adults, 91,96,98,99 suggesting a prevalence of approximately 20% in this younger population. The best data on infants 65,71,73,100 have established a prevalence of approximately 40%, with incidence of 16% as assessed by the highly sensitive electroretinogram (ERG) 30-Hz flicker amplitude. The prevalence of cone B-wave amplitude abnormalities, the other vigabatrin-specific ERG parameter that is sensitive and specific for the vigabatrin-induced defect, is about 20%, with an incidence of 4%.…”
Section: Prevalence Onset and Progression Of Vfd With Vigabatrinmentioning
confidence: 99%
“…In adults, the amplitude of the electroretinogram (ERG) response to full-field 30-Hz flickering light has been reported to be a predictor of visual field defects [15,16] and to be correlated with the severity of the field defect [12]. Other photopic [6,12,[15][16][17][18][19][20][21][22][23][24][25] and scotopic [6,7,12,14,19,20,22] ERG response parameters have also been reported to be abnormal in VGB users. However, consistent association of any of these ERG abnormalities with visual deficits has not been established.…”
Section: Introductionmentioning
confidence: 99%